Calcium Density of Coronary Artery Plaque and Risk of Incident Cardiovascular Events - Criqui, Michael H; Denenberg, Julie O; Ix, Joachim H; McClelland, Robyn L; Wassel, Christina L; Rifkin, Dena E; Carr, Jeffrey J; Budoff, Matthew J; Allison, Matthew A (JAMA : the journal of the American Medical Association, 2014)
IMPORTANCE Coronary artery calcium (CAC), measured by computed tomography (CT), has strong predictive value for incident cardiovascular disease (CVD) events. The standard CAC score is the Agatston, which is weighted upward for greater calcium density. However, some data suggest increased plaque calcium density may be protective for CVD. OBJECTIVE To determine the independent associations of CAC volume and CAC density with incident CVD events. DESIGN, SETTING, AND PARTICIPANTS Multicenter, prospective observational MESA study (Multi-Ethnic Study of Atherosclerosis), conducted at 6 US field centers of 3398 men and women from 4 race/ethnicity groups; non-Hispanic white, African American, Hispanic, and Chinese. Participants were aged 45-84 years, free of known CVD at baseline, had CAC greater than 0 on their baseline CT, and were followed up through October 2010. MAIN OUTCOMES AND MEASURES Incident coronary heart disease (CHD) and all CVD events RESULTS During a median of 7.6 years of follow-up, there were 175 CHD events and an additional 90 other CVD events for a total of 265 CVD events. With both lnCAC volume and CAC density scores in the same multivariable model, the lnCAC volume score showed an independent association with incident CHD, with a hazard ratio (HR) of 1.81 (95% CI, 1.47-2.23) per standard deviation (SD = 1.6) increase, absolute risk increase 6.1 per 1000 person-years, and for CVD an HR of 1.68 (95% CI, 1.42-1.98) per SD increase, absolute risk increase 7.9 per 1000 person-years. Conversely, the CAC density score showed an independent inverse association, with an HR of 0.73 (95% CI, 0.58-0.91) per SD (SD = 0.7) increase for CHD, absolute risk decrease 5.5 per 1000 person-years, and an HR of 0.71 (95% CI, 0.60-0.85) per SD increase for CVD, absolute risk decrease 8.2 per 1000 person years. Area under the receiver operating characteristic curve analyses showed significantly improved risk prediction with the addition of the density score to a model containing the volume score for both CHD and CVD. In the intermediate CVD risk group, the area under the curve for CVD increased from 0.53 (95% CI, 0.48-0.59) to 0.59 (95% CI, 0.54-0.64), P = .02. CONCLUSIONS AND RELEVANCE CAC volume was positively and independently associated with CHD and CVD risk. At any level of CAC volume, CAC density was inversely and significantly associated with CHD and CVD risk. The role of CAC density should be considered when evaluating current CAC scoring systems.